Adaptive Optics at Optical Wavelengths: Test Observations of Kyoto 3DII Connected to Subaru Telescope AO188. (23rd June 2016) - Matsubayashi, K.; Sugai, H.; Shimono, A.; Akita, A.; Hattori, T.; Hayano, Y.; Minowa, Y.; Takeyama, N.
Abstract: Adaptive optics (AO) enables us to observe objects with high spatial resolution, which is important in most astrophysical observations. Most AO systems are operational at near-infrared wavelengths but not in the optical range, because optical observations require a much higher performance to obtain the same Strehl ratio as near-infrared observations. Therefore, to enable AO-assisted observations at optical wavelengths, we connected the Kyoto Tridimensional Spectrograph II (Kyoto 3DII), which can perform integral field spectroscopy, to the second generation AO system of the Subaru Telescope (AO188). We developed a new beam-splitter that reflects light below 594 nm for the wavefront sensors of AO188 and transmits above 644 nm for Kyoto 3DII. We also developed a Kyoto 3DII mount at the Nasmyth focus of the Subaru Telescope. In test observations, the spatial resolution of the combined AO188–Kyoto 3DII was higher than that in natural seeing conditions, even at 6500 Å. The full width at half maximum of an undersampled (1.5 spaxels) bright guide star (7.0 mag in the V -band) was 0.″12.